Malta : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Malta showed good economic performance in the past years, reflecting its strengthened policy, and a benign external environment. Executive Directors appreciated the fiscal consolidation and structural reforms, and noted that the country remained vulnerable to investment shocks and short-term capital flows. They emphasized that steps should be taken to secure fiscal deficit reduction in the short- and medium-terms, and also to strengthen the financial system, exchange rate regime, and monetary policy. They agreed that the country's database is adequate for surveillance, but requires further strengthening.